Heeding the CALL (Comprehensive Assessment of Leadership for Learning): An inquiry into instructional collaboration among school professionals. Issue 2 (11th April 2016) - Min, Sookweon; Modeste, Marsha E.; Salisbury, Jason; Goff, Peter T.
Abstract : Purpose: – The purpose of this paper is to examine what school leadership practices are associated with a school's level of instructional collaboration among school professionals and also investigates what school characteristics are linked to the level of instructional collaboration in a school. Design/methodology/approach: – This study drew data from the Comprehensive Assessment of Leadership for Learning (CALL) survey. CALL is a multi-source measure of distributed leadership, comprised of five domains of school leadership practices. Responses from 3, 767 teachers and 167 administrators working at 129 schools were analyzed using ordinary least squares regression analysis. Findings: – The findings show that there are significant relationships between school leadership practices and the extent of instructional collaboration taking place within schools, both in terms of quantity and quality. In particular, school leadership practices that are closely related to facilitating instruction and allocating resources are associated with a school's instructional collaboration, whereas a leadership practice related to environmental factors tends not to be significantly correlated with a school's collaborative culture. This study also found that leadership perspectives on instructional collaboration are an important predictor of both quantity and quality of collaboration among school professionals. Originality/value: – This study clarifies the importance of school leadership in a collaborative culture and also provides empirical evidence of what specific practices of school leadership predict the frequencies of professional collaborative activities in school as well as their quality. In addition, this study demonstrates how schools' contextual factors are related to the level of instructional collaboration among professionals.